2009
DOI: 10.1002/jez.b.21293
|View full text |Cite
|
Sign up to set email alerts
|

Conflict and resolution between phylogenies inferred from molecular and phenotypic data sets for hagfish, lampreys, and gnathostomes

Abstract: One of the most problematic issues in vertebrate phylogenetics is the disagreement between phenotypic and molecular inferences regarding the relationships among hagfishes, lampreys, and gnathostomes. Phenotypic characters support monophyly of lampreys and gnathostomes, whereas nearly all published analyses of molecular data sets support monophyly of hagfishes and lampreys. In this study I present results of phylogenetic analyses of combined phenotypic and molecular data sets that focus on relationships among h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 73 publications
1
29
0
Order By: Relevance
“…Cartilaginous fish taxa are indicated in black. The scale shows divergence times according to molecular clock estimations [24]. The cyclostome (jawless fish) divergence is problematic [5], shown here by a balance of dating from fossil evidence and by gene sequence (www.timetree.org).…”
Section: Figurementioning
confidence: 99%
“…Cartilaginous fish taxa are indicated in black. The scale shows divergence times according to molecular clock estimations [24]. The cyclostome (jawless fish) divergence is problematic [5], shown here by a balance of dating from fossil evidence and by gene sequence (www.timetree.org).…”
Section: Figurementioning
confidence: 99%
“…Morphologists who defended cylostome paraphyly argued that molecular sequence-based trees were inconclusive because of the uncertainty as to the outgroups of the vertebrates (i.e., their closest relatives and either tunicates of amphioxus) (Fig. 1) or because of biases in the methods of molecular tree reconstruction that were at odds with the original standard parsimony methods of cladistics (9). Clearly, a third independent source of characters was needed to resolve this conflict, and much hope was put in developmental data for deciding whether hagfishes were actually primitive and had lost many characteristics since their divergence from other vertebrates (10).…”
mentioning
confidence: 99%
“…Indeed, an analysis of combined morphological and molecular datasets has suggested that the signal of cyclostome paraphyly in morphological datasets is stronger than the signal for monophyly from molecular data (39). The interrelationships of hagfish, lampreys, and gnathostomes thus remain uncertain, and this has become a classic example of phylogenetic conflict between morphological and molecular data (7,39). If morphological phylogenies are correct, hagfish provide an experimental model for investigating the evolutionary assembly of the vertebrate body plan shared by lampreys and gnathostomes.…”
mentioning
confidence: 99%